Using a combination of conservative and enucleating treatment to treat a large dentigerous cyst - Fahad Khan; Brian Castling (Elsevier, 2022)
Dentigerous cysts are the second most common type of odontogenic cysts. Although the majority of dentigerous cysts are relatively small in size, our case report is based on a patient with a very large dentigerous cyst, which is not a common occurrence. We performed a combination of conservative treatment and enucleation to prevent fracture and preserve vital structures in a two-staged approach.